Comparative Evaluation of Bandage Contact Lenses and Eye Patching after Bilateral Cataract Surgery. (13th August 2021) - Jing, Dalan; Deng, Aihua; Wang, Hongmei; Chou, Yilin; Jiang, Xiaodan; Chen, Zhenxiang; Li, Xuemin; Wen, Tingyi
Abstract : Purpose . To comparatively evaluate the safety and satisfaction of bandage contact lens (BCL) and eye patching in patients after cataract surgery. Methods . Sixteen (32 eyes) patients who planned to undergo bilateral cataract surgery were recruited. The two eyes of each patient were randomly divided into 2 groups. Group A and Group B were instructed to wear BCLs immediately at the end of the surgery until one week and eye patch immediately after surgery until one day, respectively. Visual analog scales of ten specific symptoms, Visual Function Index (VF-14) questionnaire, and best-corrected visual acuity (BCVA) were conducted on the first day before the surgery and Day 1 and Day 7 after surgery. Oculus keratography was conducted on the first day before surgery and on Day 7. Patient satisfaction was determined on Day 1. Moreover, bacterial species in the conjunctival sac, meibomian gland secretions, and BCLs were subsequently identified using 16S rRNA gene sequencing. Results . The patient satisfaction scores of Group A were higher than Group B. Group A were more motivated to choose the same treatment and were more likely to recommend BCLs to others. No statistically significant differences were found in bacterial culture positivity between the groups. The differences in ocular signs and symptoms between the two groups were not statistically significant. There were no significant differences in the BCVA and VF-14 between the groups at any time point. Conclusions . BCLs could be safely and effectively used in patients after cataract surgery.